Design of Piled-Raft using the PLAXIS 3D - مبارك, ثراء (Latakia University Journal -Engineering Sciences Series, 2025)
The traditional design of piles in the foundations of piled-raft buildings assumes that the total loads of the building are distributed only to the piles, and the role of the raft as a structural element that transfers the load to the piles is limited only, as the method adopted in the Syrian Arab code. Therefore, many piles increase the economic cost of piled-raft foundations.In this research, the pilled-raft of a 16-story residential building in Latakia was modeled using the PLAXIS 3D program to determine the percentage of the contribution of both the raft and the piles from the total loads of the building and compared with the proposed simplified method of calculating the contribution of the raft, which is based on the principle of the additional effect of the piles as raft columns, which reduces their settlement, the raft's contribution reached 21.11%, thus reducing the number of piles, which became 99 piles with 2m spacing instead of 120 piles with 1.8m spacing in the case of neglecting the raft's contribution, It is possible to consider this method safe to use compared to the Poulos method, which gave a higher percentage of the raft contribution, reaching 36.8%, compared to the analytical model of PLAXIS 3D program, which reached 28.36%.